Negative correlation between relative fat mass and bone mineral density: NHANES 2011–2018 - Jiang, Xing-An; Zhang, Hong-Li; Ye, Bin-Tao; Fang, Shao-Qi; Zhang, Jia-Jin; Yu, Hao-Lin; Liang, Jun-Bo (Frontiers in Public Health, 2025)
BackgroundUtilizing data from the National Health and Nutrition Examination Survey (NHANES), this study investigated the association between Relative Fat Mass (RFM) and lumbar spine bone mineral density (BMD) in adults, specifically evaluating the impact of RFM on lumbar BMD and determining the consistency of this relationship across diverse populations.MethodsCross-sectional data from 9,238 adults aged ≥20 years in the 2011–2018 NHANES cycles were analyzed. Relative fat mass (RFM) values were derived through a formula incorporating waist circumference (WC) and height. The relationship between RFM and lumbar BMD was assessed through weighted multiple linear regression models, subgroup analyses, and smooth curve fitting.ResultsAfter adjusting for multiple covariates, RFM exhibited a statistically significant inverse relationship with lumbar spine BMD. In the fully adjusted model, a per-unit increment in RFM was linked to a decline of 0.0110 g/cm2 in lumbar BMD (β = −0.0110, 95% CI: −0.0132 to-0.0088; p < 0.0001). Additionally, an inflection point was detected at RFM = 20.5847 (p < 0.001), with significantly distinct correlations between RFM and lumbar spine BMD when values were above or below this point. Subgroup analyses confirmed the persistence of this inverse relationship in virtually all population subgroups stratified by demographic characteristics or health statuses.ConclusionThe analysis reveals a notable inverse relationship between RFM values and BMD measurements in the lumbar spine, suggesting that elevated RFM levels might correlate with reduced BMD and heightened susceptibility to osteoporosis (OP) development. These observations highlight the critical role of evaluating adipose distribution patterns when devising preventive measures against OP and support employing RFM as an potential indicator for initiating early clinical interventions aimed at mitigating bone density deterioration.